2021
DOI: 10.1002/prca.202100036
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis identified potential age‐associated prognostic biomarkers in pneumonia‐derived paediatric sepsis

Abstract: Purpose: Our aim was to investigate the age-associated plasma protein profiles in pneumonia-derived sepsis between infants and toddlers and identify potential ageadapted prognostic markers for poor outcome of pneumonia-derived pediatric sepsis.Experimental Design: A nested case-control study strategy was applied. The plasma proteomes of pneumonia-derived pediatric septic patients with different outcomes between infants and toddlers were respectively analysed compared to their agematched controls.Results: Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The protein-protein interaction analysis of the differentially expressed proteins between the sepsis and healthy groups identi ed the top ve nodes with the highest degrees as ALB (36), AHSG (28), APOA1 (28), APOB (27), and A2M (25) (see Fig. 2E).…”
Section: Protein-protein Interaction Network Of Differentially Expres...mentioning
confidence: 99%
“…The protein-protein interaction analysis of the differentially expressed proteins between the sepsis and healthy groups identi ed the top ve nodes with the highest degrees as ALB (36), AHSG (28), APOA1 (28), APOB (27), and A2M (25) (see Fig. 2E).…”
Section: Protein-protein Interaction Network Of Differentially Expres...mentioning
confidence: 99%
“…Due to the high cost of experimental tests, only a few researchers used proteomics for pediatric sepsis biomarker screening. Luo et al 79 have performed a quantitative identification of plasma proteome to analyze the age-related proteomic profile of sepsis in children. They found that developmental age may affect the levels and biological functions of haptoglobin and thrombin-reactive protein 1 (THBS1).…”
Section: Biomarkers Screened By Proteomicsmentioning
confidence: 99%
“…Due to the high cost of experimental tests, only a few researchers used proteomics for pediatric sepsis biomarker screening. Luo et al 79 . have performed a quantitative identification of plasma proteome to analyze the age‐related proteomic profile of sepsis in children.…”
Section: Biomarkers Screened By Proteomicsmentioning
confidence: 99%
“… 8 Others suggested that cholesterol metabolism and the elevated levels of several apolipoproteins may have a protective effect on the disease. 9 , 10 So, a firmed conclusion has not been drawn until then.…”
Section: Introductionmentioning
confidence: 99%